Comparative assessment of late toxicity in patients of carcinoma cervix treated by radiotherapy versus chemo-radiotherapy – Minimum 5 years follow up. (2018) - Misra, Shagun; Lal, Punita; Kumar EP, Saibish; Rastogi, Neeraj; Tiwari, Anu; Singh, Shalini; Das, K.J. Maria; Kumar, Shaleen
Abstract: Background: A randomised trial was carried out comparing chemo-radiation (CTRT) vs. radiotherapy (RT) in patients of carcinoma cervix and showed similar rates of pelvic disease control, disease free survival and overall survival. Late toxicity is presented. Methods: Between December 2000 and July 2006, 180 patients of carcinoma cervix were randomly assigned to RT + weekly cisplatin (n = 94) or RT alone (n = 86). Late toxicity was prospectively scored using RTOG criteria in 156 evaluable patients, 79 and 77 respectively and is presented as crude incidence for rectum, bladder, small intestine, vagina, skin and bone and also as actuarial incidence for rectum and bladder. Results: The median follow up of surviving patients was 10.4 years (minimum – 6.5 years). Crude incidence, CTRT vs. RT, of late toxicities were: rectal (7.5% vs. 5%, p = 0.22), bladder (15% vs. 10.4%, p = 0.76), small bowel (3% vs. 1.2%, p = 0.51), vagina (25% vs. 35%, p = 0.35) while the actuarial risk of grades 3–5 rectal and bladder toxicities by 5 years were 13% vs. 10% (p = 0.698) and 16% vs. 14.8% (p = 0.783) respectively. Bladder toxicity appeared later then rectal toxicity (median 49.4 vs. 21.4 months). Severe bone toxicity (fractures) were higher in the CTRT arm, 5% vs. 0%, p = 0.018. On multivariate analysis vaginal involvement (p = 0.016) and bulky tumor (p = 0.020) were associated with severe vaginal morbidity while rectal point dose > 80% (p = 0.040) was associated with a higher incidence of rectal toxicity. Conclusion: Bone toxicity was significantly increased by addition of CT to RT and patients continued to experience toxicity at longer periods of follow up albeit disease free. Highlights: Late toxicity in patients of carcinoma cervix undergoing chemo/radiotherapy is underreported in randomised clinical trials. One of the first randomised trials with adequate followup reporting no significant differences in incidence of late toxicity, time course and evolution in patients of carcinoma cervix treated with radiotherapy or chemoradiotherapy in majority organ at risk. Bone fractures are increased with addition of chemotherapy while vaginal toxicity has the highest incidence. Rectal toxicity precedes bladder toxicity in incidence and resolution. Prospective documentation and long term followup are essential to get a true estimate of late morbidity.